STUDI KARAKTERISTIK DAN UKURAN TUBUH ANTARA KAMBING JANTAN BOERAWA G1 DAN G2 PADA MASA DEWASA TUBUH DI DESA CAMPANG KECAMATAN GISTING KABUPATEN TANGGAMUS - Priyo Nugroho; Idalina Harris; Kusuma Adhianto (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
This research was conducted using a survey method in Campang Vilage, District Gisting, Tanggamus conducted inJune 2012. Parameters observed in this study that the characteristic of livestock (hair color, face shape and earlength) and body size (body weight, chest circumference, body length and shoulder height).Goat Boerawa G1 andG2 samples each 60 tail. Qualitative data on the characteristic analyzed with descriptive analyzed, while quantitativedata were analyzed by T-test to determine the difference between G1 and G2 of each variable. Result of this studyindicate that the shape of the face goat G2 Boerawa flat and thick. The average length of ear G1 and G2 21,13 cm19,65 cm. Chest girth, body length and body weight Boerawa male goat G2 greater than G1: average chestcircumference 78,15> <71,97 cm body length of 66,14> <63,90cm; weight 41,45> <34,85 kg, while the shoulderheight G2 is lower than G1 the 65,77> <71,16cm.